Post-2001 Afghanistan : A critical analysis of the US WoT and state-building discourse(s) - Halimzai, Pamir (2021)
How the US discourses on War on Terror and state-building in Afghanistan have taken shape, became dominant over the past 19 years and what are their consequences? Also, in what ways both discourses are representative of wider depoliticization of the society and paved the way for the illiberal, oppressive politics of confinement and necropolitics? These questions remain at the heart of this dissertation which, breaking away from rationalist and positivist convictions, does not frame and construct Afghanistan as a problem but instead, employs a poststructuralist theoretical toolkit coupled with Critical Discourse Analysis as a methodological framework and problematizes the discourses of three US presidents –George W. Bush, Barack Obama, and Donald Trump– vis-à-vis post-2001 Afghanistan. It argues that since Afghanistan is in a state of war for almost two decades, therefore the US discourse on War on Terror and the discourse of state-building imply each other, examining them independent of each other breaks down the holistic context and mars plausible explanations and conclusions. The dissertation offers an alternative history of Afghanistan which is deemed imperative to investigate the US War on Terror and state-building discourses and likewise reinterprets the Talibanization as a reverse state-building discourse, practice, and process. Afterwards, it revisits and offers a detailed analysis of the discourses of the three US presidents revealing a concatenation despite profound ideological differences among them. The US discourses thus remain stable yet keep expanding beyond Afghanistan. The study maintains that the US discourses could not tackle terrorism as a problem effectively and could not succeed in building robust security, democratic and economic apparatuses in Afghanistan. In its place, the US discourses paved the way for the emergence of phenomena that have resulted in a total subjugation of Afghanistan and its people.